Pengaruh Need For Achievement, Locus Of Control Dan Self Efficacy terhadap Peningkatan Minat Berwirausaha di Kalangan Mahasiswa - Jullimursyida, Jullimursyida; Bachri, Nauval; Chandra, Julian (Jurnal Kinerja Kependidikan (JKK), 2019)
The purpose of this study was to identify factors that contribute to the intention of student entrepreneurs in Aceh from the aspect of the desire need for achievement, locus of control, and self-efficacy. This research is quantitative research which applied the survey approach to be able to determine the intention of entrepreneurs among students. The results indicates that only locus of control can explain the intention of students to be entrepreneurs in Aceh . The results of this research will hopefully help to clarify aspects of the development of entrepreneurship among the students that will enrich their knowledge of entrepreneurship especially among the students in Indonesian. The result of this study will be able to take a step closer to finding ways to increase the number of students to become entrepreneurs.